An investigation into collocational errors in writing of second-year students at university of foreign language studies, university of danang (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Collocations are one of the areas generally considered problematic for EFL learners. Therefore, the purpose of this thesis was to investigate the collocational errors in EFL university students’ writing in Vietnam. A total of 100 sophomores at University of Foreign Language Studies, University of Danang participated in this study. A hundred assignments and a hundred in-class practice were collected and analyzed for collocational errors. The unacceptable grammatical and lexical collcational errors were identified based on the modified version originally proposed by Benson, et al. [6] and Chen’s [16] modified version. The Oxford Advanced Learner’s Dictionary [52], the Oxford Collocations Dictionary for Students of English [53], and the British National Corpus were employed to analyze participants’ collocational errors and to provide suggestions for correction. A total of 376 collocational errors (223 grammatical collcational errors and 153 lexical collocational errors) were found. Results indicated that G8 (D) (V + Prep + O/ V + O + Prep + O) and L1 (V + N) errors occurred most frequently in the participants’ writing and L5 (Adv + Adj) were the least occurring errors. Ignorance of rule restrictions was the major source of collocational errors. Depending on the findings of this paper, it is suggested that further study may have larger number of participants such as all sophomores in the Department of English, other academic levels students in the Department of English or in other departments to gain a clear picture of EFL learners’ collocational errors.